Role and hallmarks of Sp1 in promoting ovarian cancer - Iyer Mahalaxmi; K.S. Santhy (Journal of Oncological Sciences, 2018)
Ovarian cancer has a poor prognosis especially due to late diagnosis, intrinsic resistance to some therapeutic drugs, increased interest in finding novel DNA – binding and transcription factor agents as a probable chemotherapy in treating ovarian the gynecological cancer. Based on many previous reports it is evident that the expression of various cellular genes are been regulated by Sp1 the transcription factor, but still a better understanding is required, about its role in developing and progressing the human cancer. Sp1 is been found playing dual role such as the activation as well as suppression of the cellular genes either converting into an oncogene or performing biological activity such as proliferation, differentiation, DNA damage response, apoptosis and angiogenesis. There are even proofs, which suggest that Sp1 has homologous forms of proteins named as Sp2 and Sp3, which also support Sp1 in contributing the progression of tumor cells. These typical characters of Sp1 and its interesting facts related to biological functions are yet to be explained clearly. Thus, in this current review, we briefly explain the role, characters and proteins associated with Sp1 family of transcription factor do contribute as a “hallmarks of cancer”. We also review the evidence suggesting that Sp1 is highly over – expressing the genes, which pay ways in promoting ovarian cancer. Thus, we conclude that targeting Sp1 one of the best diagnostic tool to detect ovarian cancer in early stages or promoting Sp1 as best therapeutic agent would be a best resolution to reduce the incidence of ovarian cancer. Keywords: Hallmark of cancer, Ovarian cancer, Sp1, Transcription factor